Here's the question you clicked on:
keeponbleeding
f(x) = sqrt(x+9); g(x) = 8x - 13 Find f(g(x))
Am I putting the g(x) in f(x) or vice versa? I know how to solve afterwards
Your g(x) becomes then new x value f(8x-13)
f(g(x))= 8sqrtx-4?
\(f(x)= \sqrt{x+9}\) Now since its f(g(x)) That is another way of saying f(8x-13). Meaning we replace our x with 8x-13 \( f(8x-13)= \sqrt{(8x-13)+9 }\) Now we have to simplify by opening the brackets \( f(8x-13)= \sqrt{(8x-4) }\) \( f(8x-13)= \sqrt{4(2x-1) }\) \( f(8x-13)= 2\sqrt{2x-1 }\)
oh ok I think I got it, Im going to try it on my last problem now. thanks so mucH!
No problem. You can always just come back here and check if you got your answer correct :)